2018
DOI: 10.18682/pd.v18i2.809
|View full text |Cite
|
Sign up to set email alerts
|

Personalidad evaluada desde estímulos inestructurados y creatividad en niños escolarizados argentinos

Abstract: El presente estudio examina la relación entre la personalidad, evaluada desde estímulos inestructurados y la creatividad, así como la existencia de un perfil de personalidad característico en niños creativos. La muestra quedó constituida por 146 niños y adolescentes de 9 a 12 años. La personalidad se estudió por medio de la versión

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Regarding the healthy use of leisure time in the population under analysis, it was observed that some activities were more prevalent than others; generally, art, sports/recreational, and socialization activities were less frequent. This information is important because, as other authors have shown 23, 24 , these activities should be proposed as strategies to promote the health of children and adolescents at social risk 25 , since they contribute to the psychosocial and physical state of children and adolescents, while at the same time promoting life skills. This fact is relevant since they could also be the activities to be promoted through different public health policies and programs in the country.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding the healthy use of leisure time in the population under analysis, it was observed that some activities were more prevalent than others; generally, art, sports/recreational, and socialization activities were less frequent. This information is important because, as other authors have shown 23, 24 , these activities should be proposed as strategies to promote the health of children and adolescents at social risk 25 , since they contribute to the psychosocial and physical state of children and adolescents, while at the same time promoting life skills. This fact is relevant since they could also be the activities to be promoted through different public health policies and programs in the country.…”
Section: Discussionmentioning
confidence: 95%